Aktualisasi Pendidikan Moral sebagai Nilai Daya Saing dalam Peningkatan Kualitas Moral Bangsa - Rahayu, Rizqi (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
Moral education is a series of basic moral principles and virtues of attitude and character (Tabi'at) that must be owned and made a habit by the child from the time of beginners until he becomes a Mukalaf, which is ready to sail the sea of life. Competitiveness is the capacity of a nation to face the challenges of international market competition and still maintain or increase its real income. To have competitiveness in improving the quality of the nation through education, of course, we must not forget our responsibility to the moral of the nation. Therefore, moral education is very important. Psychologically and socio-culturally, moral education in the individual is a function of all its potential (cognitive, affective, and psychomotor), in the context of socio-cultural interaction (in the family, school, and community), which lasts throughout life.Keyword: Moral Education; Competitiveness; Moral Nation. Abstrak Pendidikan moral adalah serangkaian prinsip dasar moral dan keutamaan sikap serta watak (tabi’at) yang harus dimiliki dan dijadikan kebiasaan oleh anak sejak masa pemula hingga dia menjadi seorang Mukalaf, yakni siap mengarungi lautan kehidupan. Daya saing adalah kapasitas bangsa untuk menghadapi tantangan persaingan pasar Internasional dan tetap menjaga atau meningkatkan pendapatan riil-nya. Untuk memiliki daya saing dalam peningkatan kualitas bangsa lewat jalur pendidikan, tentunya tidak boleh melupakan tanggung jawab kita terhadap moral bangsa.Oleh karena itu, pendidikan moral sangat penting. Secara psikologis dan sosial kultural, pendidikan moral dalam diri individu merupakan fungsi dari seluruh potensinya (kognitif, afektif, maupun psikomotorik), dalam konteks interaksi sosial kultural (dalam keluarga, sekolah, dan masyarakat), yang berlangsung sepanjang hayat.Kata Kunci: Pendidikan Moral; Daya Saing; Moral Bangsa.